1991
DOI: 10.1002/ijc.2910470623
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of E‐cadherin expression in madin darby canine kidney (MDCK) cells inside tumors of nude mice

Abstract: The 120-kDa cell-cell adhesion molecule E-cadherin is localized at the epithelial junctional complex and participates in the organization and maintenance of epithelia. The Madin Darby canine kidney (MDCK) cell line expresses E-cadherin in a stable way and forms polarized epitheloid structures in vitro. Harvey-murine-sarcoma-virus-transformed derivatives (MDCK-ras) produce malignant (i.e., invasive and metastatic) tumors in nude mice. We obtained evidence that E-cadherin is down-regulated in nude mouse tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 24 publications
10
63
0
Order By: Relevance
“…Dysfunction of the E-cadherin-mediated cell adhesion system plays an important role in acquisition of more malignant phenotype by tumor cells [31]. Experimental biological approaches also show that E-cadherin functions as an invasion-suppressor [20][21][22]. In the present study, the addition of function-blocking antibody to E-cadherin into the assay increased migratory activity of the integrin β3-transfectants, suggesting that Ecadherin plays a role in preventing the tumor cells from migrating from wound edge.…”
Section: Hoxd3-transfectants Fibronectin Is a Ligand For A Variety Osupporting
confidence: 53%
See 1 more Smart Citation
“…Dysfunction of the E-cadherin-mediated cell adhesion system plays an important role in acquisition of more malignant phenotype by tumor cells [31]. Experimental biological approaches also show that E-cadherin functions as an invasion-suppressor [20][21][22]. In the present study, the addition of function-blocking antibody to E-cadherin into the assay increased migratory activity of the integrin β3-transfectants, suggesting that Ecadherin plays a role in preventing the tumor cells from migrating from wound edge.…”
Section: Hoxd3-transfectants Fibronectin Is a Ligand For A Variety Osupporting
confidence: 53%
“…We earlier reported that the HOXD3-overexpression led the loss of E-cadherin expression in A549 cells [16]. In vitro experiments on cultured cells indicate Ecadherin has invasion-suppressing properties [20][21][22]. Therefore, we next examined the expression and function of E-cadherin in the integrin β3-overexpressing cells.…”
Section: Roles Of E-cadherin In In Vitro Wound-healing Activitymentioning
confidence: 95%
“…However, once maintained in culture for a few days, ascites cells return to an in vitro adhesion pattern (data not shown). This difference probably reflects an in vivo signal which is absent in vitro, due to a change of phenotype which has been reported (Mareel et al, 1991). Alternatively, the decreased adhesion seen in vivo may result from ligand occupation of the binding sites (Wilhelm et al, 1988) and OVCAR 3 ascites are found to contain glandular structures ex vivo which are not seen when OVCAR 3 cells are maintained in vitro similar to the situation with mouse mammary cells (Aggeler et al, 1991).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, a transgenic mouse model of pancreatic β cell carcinoma revealed that loss of E-CD expression coincided with transition from well differentiated adenoma to invasive carcinoma (Perl et al, 1998). However, some studies have indicated that the loss of E-CD is reversible, for example in ras-transformed Madin Darby Canine kidney cells in nude mice, possibly due to interaction with the host environment (Mareel et al, 1991). Dysfunction of α-catenin has also been implicated.…”
mentioning
confidence: 99%